Response to Professor Fadel and Professor Iqtidar - Sherman Jackson (International Institute of Islamic Thought, 2017)
Professor Fadel sees me as claiming that the Islamic secular “places jurisdictional boundaries on what religion can rightfully claim, thereby creating a legitimate space for non-religious, i.e., ‘secular’ reason.” What actually I argued, however, was that Sharia placed limits on its own shar‘ī jurisdiction, obviating the necessity-cum-legitimacy not of non-religious, secular reason but of religious secular reason. He appears to be unable to transcend the commonly held dichotomy between the secular and the religious (which my article calls directly into question) and thus to recognize the reality of the “Islamic secular” as I define it. This underwrites a profound misreading of my thesis ...